Pharmacokinetics and Potential Advantages of a New Oral Solution of Levothyroxine vs. other Available Dosage Forms - Yue, C. S.; Scarsi, C.; Ducharme, M. P. (Arzneimittelforschung, 2012)
To better understand the pharmacokinetics and potential advantages of a levothyroxine oral solution vs. tablets and soft gel capsules.4 randomized, 2-treatment, single-dose (600 mcg levothyroxine), 2-way crossover bioequivalence studies in 84 healthy subjects were analyzed. Samples were collected before dosing and until 48–72 h post-dose to calculate noncompartmental baseline-adjusted pharmacokinetic parameters: maximum concentration, time to maximum concentration, and area-under-the-concentration-time-curve from 0 to 48 h and from 0 to 2 h.Mean pharmacokinetic parameters (±standard deviation) for tablets, capsules and solution, respectively, were: area-under-the-concentration-time-curve from 0 to 2 h (ng*h/mL)=68.4±32.8, 64.4±24.4, 99.1±22.7; area-under-the-concentration-time-curve from 0 to 48 h (ng*h/mL)=1 632±424, 1 752±445, 1 862±439; maximum concentration (ng/mL)=67.6±20.9, 68.0±15.9, 71.4±16.0; time of maximum concentration (hours)=2.25±0.99, 2.38±1.58, 1.96±1.07. Overall rate and extent of exposure were not statistically different between formulations, but a faster onset of absorption for the solution was suggested (greater area-under-the-concentration-time-curve from 0 to 2 h and faster time to maximum concentration by an average of 30 min).Levothyroxine rate and extent of exposure are similar between tested formulations. The solution appears however to reach systemic circulation quicker as dissolution is not needed before absorption starts. The solution’s greater early exposure and a faster time to maximal concentration of around 30 min may be of benefit to minimize drug-food interactions and deserves further investigations.
Keywords: pharmacokinetics; levothyroxine; equivalence; solution; tablet; capsule